Immanence and Desire: Deleuze and the Political - Smith, Daniel W. (Stasis, 2019)
Spinoza posed the fundamental problem of politics as a question of desire: Why do humans fight for their servitude as if it were their salvation? Why does desire desire its own repression? Gilles Deleuze and Félix Guattari take up this question in Anti-Oedipusand attempt to provide a rigorous response. Whereas Plato defined desire in terms if lack (if I desire something, it is because I lack it), Kant effected a revolution in thought by defining desire in terms of production (because I desire something, I produce it). It is this productive concept of desire that allows Deleuze and Guattari to effect a synthesis between Freud (libidinal economy) and Marx (political economy), though as I argue Deleuze and Guattari’s deeper points of reference are Spinoza and Nietzsche. We conclude by analyzing Deleuze and Guattari’s relation to the question of a democratic politics.